Ex vivo explant model of adenoma and colorectal cancer to explore mechanisms of action and patient response to cancer prevention therapies. (25th November 2022) - Khan, Sam; Miles, Gareth J; Demetriou, Constantinos; Sidat, Zahirah; Foreman, Nalini; West, Kevin; Karmokar, Ankur; Howells, Lynne; Pritchard, Catrin; Thomas, Anne L; Brown, Karen
Abstract: Colorectal cancer (CRC) is the second leading cause of cancer death in the UK. Novel therapeutic prevention strategies to inhibit the development and progression of CRC would be invaluable. Potential contenders include low toxicity agents such as dietary-derived agents or repurposed drugs. However, in vitro and in vivo models used in drug development often do not take into account the heterogeneity of tumours or the tumour microenvironment. This limits translation to a clinical setting. Our objectives were to develop an ex vivo method utilizing CRC and adenoma patient-derived explants (PDEs) which facilitates screening of drugs, assessment of toxicity, and efficacy. Our aims were to use a multiplexed immunofluorescence approach to demonstrate the viability of colorectal tissue PDEs, and the ability to assess immune cell composition and interactions. Using clinically achievable concentrations of curcumin, we show a correlation between curcumin-induced tumour and stromal apoptosis ( P < .001) in adenomas and cancers; higher stromal content is associated with poorer outcomes. B cell (CD20 +ve ) and T cell (CD3 +ve ) density of immune cells within tumour regions in control samples correlated with curcumin-induced tumour apoptosis ( P < .001 and P < .05, respectively), suggesting curcumin-induced apoptosis is potentially predicted by baseline measures of immune cells. A decrease in distance between T cells (CD3 +ve ) and cytokeratin +ve cells was observed, indicating movement of T cells (CD3 +ve ) towards the tumour margin ( P < .001); this change is consistent with an immune environment associated with improved outcomes. Concurrently, an increase in distance between T cells (CD3 +ve ) and B cells (CD20 +ve ) was detected following curcumin treatment ( P < .001), which may result in a less immunosuppressive tumour milieu. The colorectal tissue PDE model offers significant potential for simultaneously assessing multiple biomarkers in response to drug exposure allowing a greater understanding of mechanisms of action and efficacy in relevant target tissues, that maintain both their structural integrity and immune cell compartments.